Assessing the efficiency of science, technology and innovation using Data Envelopment Analysis (DEA): The case of Colombia (2017)
This paper provides insights into how to approach the assessment of scientific production efficiency using Data Envelopment Analysis (DEA). The methods employed in this paper take into account both the CCR and Assurance Region (AR) models, which are based on science, technology and innovation (STI) indicators. The sample focuses on the departments in Colombia as well as the Capital District (C.D.). The research concludes that both models calculate the efficiency of the units of analysis. Furthermore, according to the country’s STI targets, AR is susceptible to hierarchies generated within the variables.